Coadministration of Rifampin Significantly Reduces Odanacatib Concentrations in Healthy Subjects. (1st August 2016) - Stoch, S. Aubrey; Ballard, Jeanine; Gibson, Christopher; Kesisoglou, Filippos; Witter, Rose; Kassahun, Kelem; Zajic, Stefan; Mehta, Anish; Brandquist, Christine; Dempsey, Cynthia; Stypinski, Daria; Reitman, Marc L.
Abstract: This open‐label 2‐period study assessed the effect of multiple‐dose administration of rifampin, a strong cytochrome P450 3A (CYP3A) and P‐glycoprotein inducer, on the pharmacokinetics of odanacatib, a cathepsin K inhibitor. In period 1, 12 healthy male subjects (mean age, 30 years) received a single dose of odanacatib 50 mg on day 1, followed by a 28‐day washout. In period 2, subjects received rifampin 600 mg/day for 28 days; odanacatib 50 mg was coadministered on day 14. Blood samples for odanacatib pharmacokinetics were collected at predose and on day 1 of period 1 and day 14 of period 2. Coadministration of odanacatib and rifampin significantly reduced odanacatib exposure. The odanacatib AUC0–∞ geometric mean ratio (90% confidence interval) of odanacatib + rifampin/odanacatib alone was 0.13 (0.11–0.16). The harmonic mean ± jackknife standard deviation apparent terminal half‐life (t½ ) was 71.6 ± 10.2 hours for odanacatib alone and 16.0 ± 3.4 hours for odanacatib + rifampin, indicating greater odanacatib clearance following coadministration with rifampin. Samples were collected in period 2 during rifampin dosing (days 1, 14, and 28) and after rifampin discontinuation (days 35, 42, and 56) to evaluate the ratio of plasma 4β‐hydroxycholesterol to total serum cholesterol as a CYP3A4 induction biomarker; the ratio increased ∼5‐fold over 28 days of daily dosing with 600 mg rifampin, demonstrating sensitivity to CYP3A4 induction.